2015
DOI: 10.1038/ncomms8398
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 regulates somatic cell reprogramming and pluripotency maintenance

Abstract: The generation of induced pluripotent stem (iPS) cells holds great promise in regenerative medicine. The use of the transcription factors Oct4, Sox2, Klf4 and c-Myc for reprogramming is extensively documented, but comparatively little is known about soluble molecules promoting reprogramming. Here we identify the secreted cue Netrin-1 and its receptor DCC, described for their respective survival/death functions in normal and oncogenic contexts, as reprogramming modulators. In various somatic cells, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 34 publications
(65 reference statements)
1
30
0
Order By: Relevance
“…A NuRD complex containing CHD4 and MBD3 also regulates the differentiation of ESCs, interacting with zinc finger protein of the cerebellum 2 (Zic2) at ESC enhancers (Luo et al, 2015). In agreement with the above findings, CHD proteins are crucial for reprogramming somatic cells to a pluripotent state, and both the NuRD complex and CHD1 improve reprogramming efficiency (Gaspar-Maia et al, 2009;Ozmadenci et al, 2015). Thus, CHD1 and CHD-containing NuRD complexes appear to have roles similar to those of BAF complexes during pre-implantation development and ES cell pluripotency.…”
Section: Developmental Roles Of Chd Complexessupporting
confidence: 68%
“…A NuRD complex containing CHD4 and MBD3 also regulates the differentiation of ESCs, interacting with zinc finger protein of the cerebellum 2 (Zic2) at ESC enhancers (Luo et al, 2015). In agreement with the above findings, CHD proteins are crucial for reprogramming somatic cells to a pluripotent state, and both the NuRD complex and CHD1 improve reprogramming efficiency (Gaspar-Maia et al, 2009;Ozmadenci et al, 2015). Thus, CHD1 and CHD-containing NuRD complexes appear to have roles similar to those of BAF complexes during pre-implantation development and ES cell pluripotency.…”
Section: Developmental Roles Of Chd Complexessupporting
confidence: 68%
“…Many of these TLR3 activated genes have been implicated in early brain cell fate decisions. Netrin1 is a secreted protein that works in conjunction with its dependence receptor DCC (Deleted in Colorectal Carcinoma) to regulate various pathways involved in axon guidance, apoptosis, neural cell death and cellular reprogramming (Bin et al, 2015; Furne et al, 2008; Ozmadenci et al, 2015). The role of NTN1 has been shown in vivo in floxed and null NTN1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SALL4 can interact with the Nucleosome Remodeling and Histone Deacetylation (NuRD) complex 3949 . MBD3, an essential structural component of the NuRD complex, has been shown to be a key regulator in the reprogramming process 50515253 . Though it has been suggested that the SALL4/NuRD interaction may not be required in iPSC reprogramming in a cell fusion model 45 , it remains to be seen whether the same conclusion can be drawn from other approaches in generating iPSCs.…”
Section: Function Of Sall4 In Stem Cells and Developmentmentioning
confidence: 99%